Percutaneous left atrial appendage closure, a safe alternative to anticoagulation for patients with nonvalvular atrial fibrillation and end‐stage renal disease on hemodialysis: A single center experience. Issue 5 (22nd December 2019) - Xipell, Marc; Flores‐Umanzor, Eduardo; Ojeda, Raquel; Arias, Marta; Cepas‐Guillén, Pedro L.; Regueiro, Ander; Freixa, Xavier; Cases, Aleix; Maduell, Francisco
Abstract: The evidence about the effectiveness and safety of oral anticoagulation in patients on hemodialysis is conflicting and scarce. Percutaneous left atrial appendage occlusion (LAAO) has demonstrated to be a valid alternative therapeutic option for stroke prevention in patients with nonvalvular atrial fibrillation (NVAF). The aim of this study is to present the outcomes of percutaneous LAAO in patients with end‐stage renal disease (ESRD) on hemodialysis and NVAF in our center. We conducted a retrospective review of clinical records, demographics, LAAO procedure, complications, and outcomes of patients with NVAF and ESRD on hemodialysis who underwent a percutaneous LAAO in our center between January 2017 and January 2019. In the period of the study, eight patients with ESRD on hemodialysis underwent a percutaneous LAAO in our center. The overall mean age was 67.5 years (range 56‐81; SD ± 7.2). All patients had permanent NVAF. The total mean dialysis duration was 8.49 years (range 0.83‐14.8; SD ± 6.2). The mean CHA2DS2‐VASc and HAS‐BLED scores were high (4.75 [SD ± 1.16] and 4.62 [SD ± 0.91], respectively). All patients had history of a major hemorrhagic event (BARC Score ≥3). Most patients ( n = 6) showed left ventricular hypertrophy, and the average LVEF was 54% (SD ± 6.5). All devices were implanted successfully. Postprocedural antithrombotic regimen prescribed was based on antiplatelet therapy. No deaths, cardioembolic events, or major bleeding (according to the BARC scale) were reported during a mean follow‐up of 14.24 months (SD ± 9.44). Percutaneous LAAO could be of particular interest in patients with NVAF and CKD in hemodialysis. Further studies will be necessary to confirm this hypothesis.